Determinants of Sustainability Reporting of Islamic Banks in Emerging Countries - Afifah Oki Nilasakti; Falikhatun Falikhatun (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2020)
This study aims to determine the effect of Islamic corporate governance and slack resources on sustainability reporting of Islamic Commercial Banks in Indonesia and Malaysia from 2015-2018. The corporate governance in this study consists of sharia supervisory board, the size, board of directors meeting, and audit committee. This is a quantitative study that used secondary data such as the annual and sustainability report. The reporting proxy was measured by the content analysis method which consisted of 78 items from the six dimensions adopted disclosure of AAOIFI. Furthermore, the analysis technique used was panel data regression with Random Effect Model (REM) as the estimation model. The results showed that the sharia supervisory board has a negative effect on sustainability reporting, while the board size, audit committee, and slack resources have a positive effect. Meanwhile, the board of directors' meeting has no effect on sustainability reporting. Therefore, the related government agencies such as Otoritas Jasa Keuangan (Financial Service Authority/FSA) and Bank Negara Malaysia are able to consider that the regulation related to the composition of sharia supervisory board for banking is in line with international ideal standards.